Translation and validation of the Saint Louis University Mental Status (SLUMS) Exam for older adults in Thailand: The SLUMS-Thai - Rungruang, Komwat; Manasatchakun, Pornpun; Polsingchan, Sarinya (Belitung Nursing Journal, 2025)
Background: The Saint Louis University Mental Status (SLUMS) Exam is a commonly used tool for screening cognitive function, particularly for detecting mild cognitive impairment (MCI) and early dementia. It was developed to overcome limitations in existing cognitive assessments by evaluating a broad range of domains, including language comprehension, executive function, memory, and attention. While effective in English-speaking populations, its use in non-English-speaking settings is limited by language and cultural differences. In Thailand, the lack of linguistically and culturally adapted cognitive screening tools can lead to inaccurate assessments. To ensure reliable and valid evaluations in older Thai adults, the SLUMS must be appropriately translated and culturally adapted. Objective: This study aimed to translate the SLUMS into Thai (SLUMS-Thai) and validate its use among older adults in Thailand. Methods: The translation process consisted of seven steps: establishing the expert team, synthesizing the translated version, forward translation, pilot testing to ensure clarity, cultural appropriateness testing, blind back-translation, and translation equivalence testing. The study involved 100 older adults. Validation was performed using descriptive statistics, Pearson’s correlations, the Index of Item-Objective Congruence (IOC), and Cronbach’s alpha coefficients. Results: The findings showed that cultural appropriateness was assessed using expert evaluations on the relevance and sensitivity of the tool to Thai cultural norms and practices, with the rate of appropriateness at the highest level (Mean = 4.97, SD = 0.71), and translation equivalence was also rated highly (Mean = 4.76, SD = 0.27). The correlation between the original SLUMS and the SLUMS-Thai was strong (r = 0.84 - 0.91). The IOC values for the 11 questions ranged from 0.80 to 1.00, and the Cronbach’s alpha coefficient was 0.83, indicating high internal consistency. The tool’s ability to differentiate between different cognitive states was proven by the Discriminant Index, which ranged from 0.23 to 0.62.  Conclusion: The SLUMS-Thai demonstrated acceptable content validity and strong psychometric properties that were linguistically and culturally appropriate. As a consequence, the SLUMS-Thai can be used to screen older persons for dementia and mild cognitive impairment in Thailand and may be helpful for modifying interventions for accurate diagnosis and cognitive function assessment.